INFLUENCE OF EXOGENOUS GIBBERELLIN AND ITS MIXTURE WITH SUCROSE ON THE FORMATION OF XYLEM INCREMENT OF SILVER BIRCH - Новицкая, Людмила Людвиговна; Тарелкина, Татьяна Владимировна; Николаева, Надежда Николаевна; Иванова, Диана Сергеевна; Семенова, Людмила Игоревна; Novitskaya, Ludmila; Tarelkina, Tatiana; Nikolaeva, Nadezhda; Ivanova, Diana; Semenova, Ludmila (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2019)
We studied the effect of gibberellin on cambial activity towards the xylem formation in adult birch trees (Betula pendula Roth var. pendula, common birch). The injection of exogenous solutions was used as a methodological technique. To do this, “chambers” were made on tree trunks by cutting out the outer layers of the bark up to the inner parts of the non-conductive phloem, leaving the conductive phloem and cambial zone intact. GA3 gibberellin solutions (0.005%, 0.01%, 0.02%, 0.05%, 0.1%, 0.2 %) and a mixture of gibberellin with sucrose (GA3 0.01% + sucrose 1% - 20%) were injected into the chambers using a syringe. A strong stimulating effect of the hormone on the formation of xylem increment has been established. It was not possible to identify the dependence of the growth increment on the concentrations used, since their values obviously exceeded the level at which the maximum possible response of the cambial zone to the action of gibberellin was achieved with a given metabolic status of cells and tissues. This is confirmed by the effect of the residual action of exogenous solutions, which manifested itself after the termination of their administration: in variants with higher concentrations of the hormone, the final increase in xylem was greater. It was demonstrated for the first time that high sucrose concentrations (10% and 20%) reduce the stimulating effect of gibberellin. It has been suggested that in this case, sucrose can act through an increase in the level of UDP-glucose, the interaction of which with gibberellin leads to its conjugation (inactivation). The reaction of UDP-glucose with auxin cannot also be excluded, as a result of which it’s the conjugate IAA-glucose is formed, since gibberellin provides acceleration of cambial growth only in the presence of physiologically active (free) auxin in the tissue.